Modeling and optimization of mixing conditions for petroleum sludge modified bitumen using response surface methodology - Memon, A.M. (Elsevier Ltd, 2020)
This study investigates the feasibility of adding petroleum sludge (PS) in bitumen to reduce the reliance on petroleum-based bitumen. This objective was achieved by modeling and optimizing the mixing conditions of petroleum sludge modified bitumen (PSMB) using response surface methodology (RSM) and physical characterization. The synergistic effects of mixing temperature and speed improved the stiffness of PSMB, while the mixing time first decreases and then increases the stiffness of PSMB. Under optimal mixing conditions, the PSMB complied with the storage stability and penetration index criteria for bitumen modification. With these findings, PS can partly substitute the bitumen and reduce the risk of waste accumulation in petroleum refineries. Â© 2020 Elsevier Ltd